The Self and Its Pleasures Bataille, Lacan, and the History of the Decentered Subject - Dean, Carolyn J. (Cornell University Press, 2016)
Why did France spawn the radical poststructuralist rejection of the humanist concept of 'man' as a rational, knowing subject? In this innovative cultural history, Carolyn J. Dean sheds light on the origins of poststructuralist thought, paying particular attention to the reinterpretation of the self by Jacques Lacan, Georges Bataille, and other French thinkers. Arguing that the widely shared belief that the boundaries between self and other had disappeared during the Great War helps explain the genesis of the new concept of the self, Dean examines an array of evidence from medical texts and literary works alike. The Self and Its Pleasures offers a pathbreaking understanding of the boundaries between theory and history. ; Why did France spawn the radical poststructuralist rejection of the humanist concept of 'man' as a rational, knowing subject? In this innovative cultural history, Carolyn J. Dean sheds light on the origins of poststructuralist thought, paying particular attention to the reinterpretation of the self by Jacques Lacan, Georges Bataille, and other French thinkers. Arguing that the widely shared belief that the boundaries between self and other had disappeared during the Great War helps explain the genesis of the new concept of the self, Dean examines an array of evidence from medical texts and literary works alike. The Self and Its Pleasures offers a pathbreaking understanding of the boundaries between theory and history.